Recovery of Pain: Psychoanalytic Reading of Stanley Kunitz’s Selected Poems - Madlool Al Jumaily, Asmaa Khalaf; Idan, Noor Salim (Journal of Tikrit University for Humanities, 2023)
This research examines Stanley Kunitz’s poems in the light of psychoanalytic reading. In particular it tackles the topic of recovery and past wounds in Kunitz’s poetic texts. Kunitz has suffered from disordered childhood because of his father’s suicide few weeks before his birth. This event is an important point which causes Kunitz’s plight and is responsible for shaping his tattered identity. Kunitz is unaware to this pain, since it is buried in the unconscious mind, which is the store for hidden pain, repressed feelings and dark wishes to reappear in his adulthood. Kunitz’s uniqueness and bravery are located in the way he confronts his wounds. This research concludes that Kunitz revisits the roots and seeds of his pain and its cause and tries to recover it.